Literature Review : Reducing Pain Intensity in Cervic Cancer Patients - Pratitis, Izzati Adha; Adhisty, Karolin (Jurnal Kesehatan Mahardika, 2022)
Along with the increasing stage of cervical cancer, patients complain of pain with higher intensity and longer duration. This makes pain a symptom with the application of important interventions in nursing care. It is said that pain comes from the patient's physical and psychological problems so that cervical cancer patients are expected to be able to control the pain. The purpose of this literature review is to provide alternative interventions that can be given to cervical cancer patients non-pharmacologically. This type of research was using the literature review method using a qualitative research approach. The selection of journal criteria can be accessed in full, the journal year is limited from the last 10 years, namely 2010-2020. The results of this literature review provide recommendations through Progressive Muscle Relaxation (PMR) and Hypnotherapy as alternative interventions that can be given to cervical cancer patients. Both of these therapies have a good effect on reducing pain intensity in various existing research applications. Keywords: Pain, Cervical Cancer, Pain Therapy